2014
DOI: 10.1155/2014/198572
|View full text |Cite|
|
Sign up to set email alerts
|

Nanopigmented Acrylic Resin Cured Indistinctively by Water Bath or Microwave Energy for Dentures

Abstract: The highlight of this study was the synthesis of nanopigmented poly(methyl methacrylate) nanoparticles that were further processed using a water bath and/or microwave energy for dentures. The experimental acrylic resins were physicochemically characterized, and the adherence ofCandida albicansand biocompatibility were assessed. A nanopigmented acrylic resin cured by a water bath or by microwave energy was obtained. The acrylic specimens possess similar properties to commercial acrylic resins, but the transvers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
1
5
0
2
Order By: Relevance
“…Suspension polymerization is adequate technically to obtain PMMA spherical microparticles with controlled sizes ranging from 5 to 1000 µm [22]. Alginate stabilizer produces microparticles from 5 to 80 µm (Figure 2a), whereas microparticles below 30 µm are obtained with gelatin stabilizer (Figure 2b) as previously reported [24][25][26]. These sizes are within the range of commercial PMMA (10 to 100 µm) used for prosthodontics (Figure 2c and d).…”
Section: Spherical Microparticles: Effect Of Stabilizer Agent On Sizesupporting
confidence: 72%
See 2 more Smart Citations
“…Suspension polymerization is adequate technically to obtain PMMA spherical microparticles with controlled sizes ranging from 5 to 1000 µm [22]. Alginate stabilizer produces microparticles from 5 to 80 µm (Figure 2a), whereas microparticles below 30 µm are obtained with gelatin stabilizer (Figure 2b) as previously reported [24][25][26]. These sizes are within the range of commercial PMMA (10 to 100 µm) used for prosthodontics (Figure 2c and d).…”
Section: Spherical Microparticles: Effect Of Stabilizer Agent On Sizesupporting
confidence: 72%
“…In this polymerization, the addition of a soluble stabilizer in water [gelatin, clay or clay derivative, cellulose derivatives, water-soluble polymers such as poly(vinyl alcohol) (PVA) or starch] helps to prevent the breakup of droplets or avoids the droplet from adhering to each other [20][21][22]24]. This process could be assisted with low temperature or ultrasonic waves [20,[24][25][26][27]].…”
Section: Suspension Polymerizationmentioning
confidence: 99%
See 1 more Smart Citation
“…This factor may be explained by some authors that reported water absorption when the acrylic resin is immersed in the aqueous environment. [ 10 14 15 ]…”
Section: Discussionmentioning
confidence: 99%
“…QC-20 resin with 3% pigment showed lower results [ Table 2 ] as displayed in Figure 2 . This fact can be associated to its fast polymerization cycle,[ 15 ] whereas the components evolved in the chemical activation can be responsible for the lowest results of superficial hardness (Knoop) since the chemically activated acrylic resins exhibit the lowest results when compared to the heat-activated. [ 17 ]…”
Section: Discussionmentioning
confidence: 99%